Lactic acid production from microwave-alkali pretreated oil palm trunk biomass using simultaneous saccharification and fermentation - Lai, Long Wee (2015)
Oil palm trunk (OPT) has never been used as a substrate in simultaneous saccharification and fermentation (SSF) for lactic acid production due to the existence of lignin in lignocellulose which makes biomass difficult to be hydrolyzed by enzymes and microbes. Hence, when used as substrate, effective pretreatment method is necessary so as to release the cellulose from complex crystalline structure. Production of lactic acid via SSF required compromising circumstances as microbe and enzyme perform best at different operating conditions. Present study demonstrated the production of lactic acid from microwave-alkali (Mw-A) pretreated OPT biomass by using cellulase, 1,4-ß-D-glucosidase and Rhizopus oryzae NRRL 395 through SSF process. The OPT biomass was treated using three different pretreatment methods: Mw-A, steam-alkali-chemical (SAC) and Mw-A + SAC techniques. Variations on physical and chemical constituents on OPT were analyzed. After pretreatment, results revealed higher amount of cellulose ( /100 biomass) was obtained for Mw-A sample, 71.88 as compared to Mw-A +SAC, 56.50 and SAC, 42.70. The 72 enzymatic saccharification revealed that accumulated glucose amount (Mw-A sample) was 4.86-fold as compared to untreated substrate. The values of enzyme kinetics parameters: Lineweaver-Burk method ( =3.682 , =4.750 ) were in close agreement with non-linear regression ( =3.422 , =4.710 ), obeying Michaelis-Menten model. Experimental design on SSF was performed by response surface methodology (RSM) using face centered central composite design. The influence of three independent variables: temperature (32–42 ), pH (4–6) and enzyme ratio (3:1–7:1) on lactic acid production were investigated. When temperature, pH and enzyme ratio were set to 36.11 , 4.56 and 5:1; experimental value was in good agreement with RSM model prediction where lactic acid production at 6.632 ± 0.032 was achieved. By performing Mw-A pretreatment; treated OPT substrate was easy to be utilized in SSF process for the production of lactic acid